Pengaruh Work-life balance dan Work Environment Terhadap Kepuasan Kerja Karyawan Gen-Z di PT. Jhonlin Agro Raya Tbk - Setianingrum, Risty; Wahono, Budi; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study examines Eksplorasi The Effect of Work-Life Balance and Work Environment on Generation Z Job Satisfaction at PT. Jhonlin Agro Raya Tbk. As digital natives, Generation Z exhibits unique needs, such as flexible working arrangements and conducive work environments, requiring organizations to adapt workplace policies to maintain their satisfaction and productivity. The research employs a quantitative method, gathering data through questionnaires distributed to 90 respondents. The results indicate that Work-life balance significantly affects job satisfaction, while Work Environment does not show a significant partial influence. Simultaneously, these two variables contribute 8.7% to job satisfaction, with the remaining 91.3% influenced by other factors. These findings imply that the company should prioritize developing policies that support employees' Work-life balance to enhance their satisfaction and loyalty.  Keywords: Work Life Balance, Work Environment, Job Satisfaction, PT. Jhonlin Agro Raya Tbk